Effect of poly-hexamethylene biguanide hydrochloride (PHMB) treated non-sterile medical gloves upon the transmission of Streptococcus pyogenes, carbapenem-resistant E. coli, MRSA and Klebsiella pneumoniae from contact surfaces - Ali, S. (BMC Infect Dis, 2017)
BACKGROUND: Reduction of accidental contamination of the near-patient environment has potential to reduce acquisition of healthcare-associated infection(s). Although medical gloves should be removed when soiled or touching the environment, compliance is variable. The use of antimicrobial-impregnated medical gloves could reduce the horizontal-transfer of bacterial contamination between surfaces. AIM: Determine the activity of antimicrobial-impregnated gloves against common hospital pathogens: Streptococcus pyogenes, carbapenem-resistant E.coli (CREC), MRSA and ESBL-producing Klebsiella pneumoniae. METHODS: Fingerpads (~1cm(2)) of PHMB-treated and untreated gloves were inoculated with 10 μL (~10(4) colony-forming-units [cfu]) of test-bacteria prepared in heavy-soiling (0.5%BSA), blood or distilled-water (no-soiling) and sampled after 0.25, 1, 10 or 15 min contact-time. Donor surfaces (~1cm(2) computer-keys) contaminated with wet/dry inoculum were touched with the fingerpad of treated/untreated gloves and subsequently pressed onto recipient (uncontaminated) computer-keys. RESULTS: Approximately 4.50log(10)cfu of all bacteria persisted after 15 min on untreated gloves regardless of soil-type. In the absence of soiling, PHMB-treated gloves reduced surface-contamination by ~4.5log(10)cfu (>99.99%) within 10 min of contact-time but only ~2.5log(10) (>99.9%) and ~1.0log(10) reduction respectively when heavy-soiling or blood was present. Gloves became highly-contaminated (~4.52log(10)–4.91log(10)cfu) when handling recently-contaminated computer-keys. Untreated gloves contaminated “recipient” surfaces (~4.5log(10)cfu) while PHMB-treated gloves transferred fewer bacteria (2.4–3.6log(10)cfu). When surface contamination was dry, PHMB gloves transferred fewer bacteria (0.3–0.6log(10)cfu) to “recipient” surfaces than untreated gloves (1.0–1.9log(10); P < 0.05). CONCLUSIONS: Antimicrobial-impregnated gloves may be useful in preventing dissemination of organisms in the near-patient environment during routine care. However they are not a substitute for appropriate hand-hygiene procedures.